Karakteristik Ekstrak Serbuk Gergajian Kayu Tembesu (Fagraea Fragrans), Rengas (Gluta Renghas) dan Medang (Litsea Sp) sebagai Larvasida Lalat Rumah (Musca Demostica) - Riana Anggraini; Jauhar Khabibi (Universitas Batanghari Jambi, 2022)
Sawdust contains polar compounds that act as insecticides such as saponin, tanin, fenoid, anthraquinones, steroid dan triterpenes. Some of these components are toxic to larvae. Therefore, it is necessary to research the potential of extracts from sawdust as a natural insecticide against house flies (Musca demostica). This study aims to analyze the characteristics and effectiveness of the sawdust extract of Tembesu wood (Fagraea fragrans), rengas (Gluta renghas), medang (Litsea sp) as larvacides of house flies (Musca demostica). The analysis of this research was analyzed using descriptive statistical variables. The main variables observed were the mortality rate of flies and extract levels of extracts of Fagraea fragrans, Gluta renghas, and Litsea sp. Preliminary results showed that the powder moisture content of Litsea sp., F. fragrans and G. renghas ranged from 12-15%. The yield of the extracts of Litsea sp., F. fragrans and G. renghas was around 2%. G. renghas extract had the greatest mortality at a concentration of 9% and 10% compared to other wood extracts.